Polynucleotide-based treatments for various facial scars including combat injuries - Kim, Michael James; Wan, Jovian; Oksana, Lopatkina; Yuliia, Lavrik; Chugay, Olena; Platonova, Olena; Sydorchuk, Olena; Yi, Kyu-Ho (The Journal of dermatological treatment, 2024)
This study examines the therapeutic efficacy of polynucleotide-based therapies, specifically REJURAN , for managing scars and burns. Scars and burns present significant challenges in dermatology, often affecting patients' quality of life. Traditional treatments can be limited in effectiveness, prompting the exploration of innovative approaches like polynucleotide therapy, which utilizes salmon DNA to stimulate tissue repair, modulate inflammation, and enhance collagen production. A series of case studies was conducted, including diverse patient profiles with various types of scars and burns. The study evaluated the impact of REJURAN on scar appearance, texture, and overall skin quality. Some cases also explored the combination of polynucleotide therapy with other treatments such as Platelet-Rich Plasma (PRP) and botulinum toxin. Notable improvements were observed across cases, including reduced scar visibility and enhanced skin texture. The therapy proved effective in treating post-traumatic, post-operative, and burn-related scars, demonstrating its versatility and potential benefits. Combination therapies showed promising results, though further research is needed. Polynucleotide-based therapy with REJURAN shows promise in scar and burn management, offering a novel approach that leverages the body's regenerative processes. Further studies are recommended to confirm these findings and refine treatment protocols.